An Advanced Control Strategy for Grid Interfaced DG to Enhance Voltage Support During Unbalanced Faults - Maganti S.; Yalla N.; Padhy N.P.; Al Beshr H.; Sadanandan S.K.; Ghaoud T. (My University, 2025)
Numerous control strategies are proposed to support the grid voltages during asymmetrical faults. Most control strategies are based on sequence-based voltage components for three-phase, three-leg inverter-based Distributed Generations(DG). Further, the reactive power injection by these control strategies affects healthy phase voltage, which limits voltage support to avoid over-voltage risk. The Three-phase, Four-leg Inverters(TFI) have recently become more popular due to their ability to supply local loads and zero sequence current control. The voltage support concept is explored less in TFI-based DGs in the case of unbalanced grid faults. In this regard, an advanced control strategy has been developed in this paper to enhance voltage support during asymmetrical grid faults. The proposed control strategy can supply zero-sequence current and reactive power injection into faulty phases without affecting healthy phase voltage magnitude, ensuring safe operating current limits. The proposed voltage support control strategy is suitable for both strong and weak voltage profiles of grids. The proposed control method is validated on a grid-interfaced, three-phase, four-leg inverter-based DG at an operating Short Circuit Ratio(SCR) of 3. The performance of the developed voltage support control strategy is validated by comparing the results with those of the conventional control strategy of the same system parameters. © 2024 IEEE.